Penerapan Dan Penggunaan Teknologi Masa Depan Dalam Novel Matahari (Unedited Version) Karya Tere Liye - Nur Ardiansyah, Taufik; Dwi Kurniawan, Eva (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
This study aims to examine the role and use of modern technology in the future as depicted in Tere Liye's novel "Matahari" (unedited version). The study employs a descriptive research method, gathering qualitative data of a descriptive nature. The findings reveal that the novel presents several futuristic technologies, including flying cars, flying shoes, flying capsules, three-dimensional map navigation, modern costumes, and wireless electricity. These technologies possess various advanced functions and applications, such as high mobility, exceptional combat capabilities, detailed spatial visualization, comfort and protection for users, and efficient electricity distribution. This study holds significance as it provides insights into the potential applications of modern technology in the future and its implications for human life. The findings can serve as a reference point for further research on future technologies and their impact on human society.